Influence of sexually transmitted infections on the cervical cytological abnormalities among Iranian women: A cross-sectional study - Azam Shafaei; Seyyed Ali Akbar Shamsian; Mohammad Ghodsi; Fatemeh Sadabadi; Maryam Shahi (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Sexually transmitted infections (STIs) are one of the world's most severe health challenges. The existence of STIs such as human papillomavirus (HPV) might cause cervical cell changes leading to cervical cancer. Objective: This study aims to assess the association of STIs with cervical cytological abnormalities and genital warts among women in northeastern Iran. Materials and Methods: This cross-sectional study was carried out on 190 women referred to the central laboratory of Academic Center for Education, Culture, and Research, Mashhad, Iran from March to July 2022. The presence of genital infections caused by Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, and Herpes simplex viruses (1 and 2) were assessed using the real-time polymerase chain reaction method. HPV genital infection was detected based on the principles of reverse hybridization, and cellular changes in the cervix were examined by the liquid-based cytology technique. Results: The mean age of participants was 35.33 ± 8.9 yr. 34 different HPV genotypes were detected in all HPV-positive cases, and the most common genotype was low-risk HPV6. No significant association was found between STIs and cervical cytology abnormalities. The prevalence rates of sexually transmitted pathogens among HPV-positive and HPV-negative individuals were 10.9 and 1.6%, respectively. The frequency of genital warts was significantly higher in cases with multiple infections of high- and low-risk HPV genotypes. Conclusion: High percentages of the participants with non-HPV STIs and HPV infection had normal cervical cytology. It is advised to use STIs and HPV diagnostic tests along with cytology examinations for cervical cancer screening.